2018
DOI: 10.28916/lsmb.2.3.2018.20
|View full text |Cite
|
Sign up to set email alerts
|

Invadopodia Formation is a Critical Step in Cancer Cell Invasion: The Effect of Passage Number on Invadopodia Formation in MDA-MB-231 Breast Cancer Cell Line

Abstract: High invasive cancer cells are thought to recruit specialised actin-rich protrusions for invasion in metastasis process. These protrusions are termed invadopodia. To study invadopodia formation, one of the first challenges faced by researchers has been to optimise the cell line passage number in order to be used for the invadopodia assay. Therefore, this study aims to investigate the effects of the passage number on invadopodia formation in MDA-MB-231 breast cancer cell line. Invadopodia assay was used to achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 27 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have reported the role of passage number in the progression of invasion and metastasis. A study by Hamad, Kqueen and Hashim ( 18 ), reported that the difference in the passage number affects the formation of invadopodia. Invadopodias are specialised actin-rich protrusions recruited by cancer cells to perform an invasion into the surroundings ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported the role of passage number in the progression of invasion and metastasis. A study by Hamad, Kqueen and Hashim ( 18 ), reported that the difference in the passage number affects the formation of invadopodia. Invadopodias are specialised actin-rich protrusions recruited by cancer cells to perform an invasion into the surroundings ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Invadopodias are specialised actin-rich protrusions recruited by cancer cells to perform an invasion into the surroundings ( 19 ). Hamad, Kqueen and Hashim ( 18 ) reported that the formation of invadopodia in MDA-MB-231 cells is influenced by the passage number of the cells. The study added that the lower passage number (P7) exhibited a higher percentage of cells that formed invadopodia as compared to the cells of higher passage number (P35).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations